Efeitos dissipativos em pontos quânticos na presença do efeito Aharonov Bohm - Cortez, Demócrito Sobreira da Cruz (2022)
In this work we analyze the effects of dissipation in a charged oscillator in the presence of the Aharonov-Bohm effect via Hamiltonians with time-dependent mass m(t). Such systems describe the dynamics of the dissipation in 2D parabolic quantum dot in the presence of Aharanov-Bohm effect. We calculate the uncertainties (Δr and Δp) and the quantum mechanical expectation value of energy (〈E〉) for two kinds of dissipations and analyzed them with respect to time (t), damping parameters and flux parameter (v). For the Caldirola-Kanai dissipation, we observed that the flux parameter v decreases the energy dissipation in a quantum dot for a certain range of t.